Urinary KIM-1 is not correlated with gestational age among 5-year-old children born prematurely - Jaime M. Restrepo; Laura Torres-Canchala; Laura Torres-Canchala; Joseph V. Bonventre; Juan C. Arias; Michael Ferguson; Adriana Villegas; Oscar Ramirez; Oscar Ramirez; Guido Filler; Guido Filler (Frontiers in Pediatrics, 2023)
BackgroundPreterm birth is associated with decreased nephron endowment. Currently, there is no reliable non-invasive biomarker to identify or monitor decreased nephron number in at-risk patients. Urinary Kidney Injury Molecule-1 (KIM-1) is a biomarker of acute and chronic renal injury. We measured urinary KIM-1 among a wide array of other potential biomarkers.MethodsWe conducted an ambispective cohort study of 5-years-old children born prematurely and healthy controls identified from city schools. Detailed anthropometrics, renal ultrasound dimensions, and biochemical parameters were measured. Urinary KIM-1 was measured using Luminex® technology. Age independent z-scores were calculated and compared. Spearman correlations were used for estimating the association between measures and KIM-1.ResultsWe enrolled 129 children, 97 (75.2%) born pre-term and 32 (24.8%) healthy controls born at full-term. Pre-term patients had significantly lower weight and body surface area than controls. Pre-term patients and controls did not differ in current age, sex, race, height, blood pressure, urinary sodium, fractional sodium excretion, serum creatinine and estimated GFR. All spearman correlation between KIM-1 and gestational age, renal and serum measurements were weak without statistical significanceConclusionIn 5-year-old children born prematurely, KIM-1 was not correlated with gestational age. Further prospective studies need to confirm this finding.